Pengaruh Spiritual Leadership Terhadap Organizational Commitment Melalui Calling Dan Membership Pada PT.Asuransi Takaful Keluarga - Romi Ilham (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2012)
Spiritual leadership is creation of values, attitude and behavior which is required to motivate one’s selves and other by intrinsic motivation to achieve spiritual survival sense through calling and membership.  Impact of spiritual leadership in developing relationship between leader and follower are value creation in harmony, empowerment of member and individual, increase psychology aspect and welfare until the organizational commitment is achieved.  The objectives of the research are to gain knowledge regarding influence of spiritual leadership to organizational commitment through calling and membership. This research was conducted to 50 employees of PT Asuransi Takaful Keluarga Marketing Office in East Java.  Analysis technique used to test the hypothesis is Partial Least Square (PLS).Based on analysis result, we conclude that: (1) spiritual leadership is has significant influence to calling (2) spiritual leadership has significant influence to membership (3) calling has significant influence to organizational commitment and (4) membership has significant influence to organizational commitment. Keywords: Spiritual Leadership, Organizational Commitment, Calling/Meaning, Membership.